SCIENCE LEARNING IN EARLY CHILDHOOD - dwiyani marsetyaningrum (IKIP Siliwangi Bandung, 2018)
Science trains children experimenting with carrying out multiple experiments, enriching children's insights to always want to try and try. So that science can lead and encourage children to be a creative and full of initiative and can build a knowledge that later can be used in adulthood. Science familiarizes children following the experimental stages and should not hide a failure. That is, science can train positive mental, logical thinking, and order (systematic). In addition, it can also train children to be careful, because children must observe, make predictions, and make decisions. The introduction of early science should be tailored to the child's developmental level and characteristics, the educator does not stuff the child with the concept but facilitates the child to discover facts and concepts in a simple experiment. Like scientists, children need skills on how to use observing, classifying, measuring, predicting, experimenting and communicating skills. Basically, activities in the concept of science can be learned through simple and simple daily experiences. Fun and exciting atmosphere will motivate the child to continuously seek answers to what the child thinks and prove because in essence the child is born with something miraculous to bring curiosity or find out about what he saw, heard and felt in the neighborhood.